Smart farming platform “GeoGoviya” launched in Sri Lanka - CGIAR Research Program on Water, Land and Ecosystems (2021)
Building on work of WLE relating to both climate insurance and climate advisories, the smart farming platform “GeoGoviya” was launched in Sri Lanka as a public–private partnership to provide real-time data to support both farmers (up to 1.8 million smallholders) and policymakers with evidence-based decision making.